2021
DOI: 10.15446/revfacmed.v70n3.92324
|View full text |Cite
|
Sign up to set email alerts
|

Diversidad y distribución de mosquitos (Diptera: Culicidae) en el Perú y su relación con las enfermedades metaxénicas

Abstract: Introducción. Los ecosistemas tropicales andinos y amazónicos determinan la gran biodiversidad presente en Perú. Sin embargo, los estudios sobre mosquitos (Diptera: Culicidae) en el país son escasos, lo que resulta en un vacío de información en cuanto a su diversidad, ecología, distribución y abundancia. Objetivo. Buscar evidencia documentada sobre la diversidad y distribución de mosquitos en el Perú, y establecer —con relación a las especies de importancia médica— su potencial vínculo con el ciclo epidemiológ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…usquatus , and Cx. camposi (Morales 1971 ; Ayala et al 2020 and Bram 1967 ). However, to date, no CoxI gene sequences have been reported for this species in Peru.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…usquatus , and Cx. camposi (Morales 1971 ; Ayala et al 2020 and Bram 1967 ). However, to date, no CoxI gene sequences have been reported for this species in Peru.…”
Section: Resultsmentioning
confidence: 99%
“…2021 ), of which in Peru, 182 species have been officially reported; of these, 44 belong to the genus Culex Linnaeus, 1758 (Ayala et al. 2020 , 2021 ) and many of these are considered arbovirus vectors, especially the species of the subgenus Melanoconion (Turell et al. 2005 ; Yanoviak et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mosquitoes of the Culicidae family represent a threat to public global health, especially in tropical and subtropical regions, where they participate as the main vectors in the transmission of infectious agents that affect humans and animals. Of the circa 3700 species of mosquitoes worldwide, 1069 species are registered in the neotropical region (Wilkerson et al, 2021), of which in Peru, 182 species have been o cially reported; of these, 44 belong to the genus Culex Linnaeus, 1758 (Ayala et al, 2020(Ayala et al, , 2021) and many of these are considered arbovirus vectors, especially the species of the subgenus Melanoconion (Turell et al, 2005;Yanoviak et al, 2005;Turell et al, 2006Turell et al, , 2008Evangelista et al, 2013;Hang et al, 2016;Treangen et al, 2016;Turell et al, 2021). In Peru, the arboviruses transmitted by Culex spp.…”
Section: Introductionmentioning
confidence: 99%
“…which limited the observation of this grouping(Demari et al, 2011;Linton et al, 2013;Viveros et al, 2022).Studies regarding the analysis of mosquitoes from Peru are limited, outdated, and concentrated only in some regions of the country, which generates a gap in the knowledge of the distribution, ecology, and diversity of the species over the Peruvian national territory(Ayala et al, 2020). In the department of Huanuco, 15 genera including 36 species of Culicidae have been registered, and of these, six are Culex species.…”
mentioning
confidence: 99%